2016
DOI: 10.1093/heapol/czw129
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopia’s health extension workers use of work time on duty: time and motion study

Abstract: Ethiopia implemented an innovative community-based health program, called the health extension program, to enhance access to basic health promotion, disease prevention and selected curative services by establishing health posts in every village, also called kebeles, with average of 5000 people, staffed with two health extension workers (HEWs). This time and motion study was done to estimate the amount of time that HEWs spend on various work duties and to explore differences in urban compared with rural setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 7 publications
2
51
1
1
Order By: Relevance
“…The community-based cross-sectional study was conducted using the Health Extension Worker (HEW) network to identify cases. HEWs are predominately female, and are recruited from the communities they serve to expand access to basic health promotion, disease prevention and selected curative health services [ 20 ]. The HEWs searched for patients affected by LF and podoconiosis in their community catchment areas, with two HEWs covering a population of approximately 5,000 people [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The community-based cross-sectional study was conducted using the Health Extension Worker (HEW) network to identify cases. HEWs are predominately female, and are recruited from the communities they serve to expand access to basic health promotion, disease prevention and selected curative health services [ 20 ]. The HEWs searched for patients affected by LF and podoconiosis in their community catchment areas, with two HEWs covering a population of approximately 5,000 people [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Health Extension Workers Time Motion Study. 15 - 17 The work activities of two HEWs in 22 Woredas (for a total of 44 HEWs) were observed for a period of 21 consecutive days between April and June 2014. Each day, observers recorded activities continuously beginning with the HEW’s first work-related task of the day upon arrival and ending when the HEW completed the last work-related task of the day before leaving for the day.…”
Section: Methodsmentioning
confidence: 99%
“… 19 , 20 For a complete description of the TMS methods and results, please refer to Ethiopia’s health extension workers use of work time on duty: time and motion study. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Other demand side barriers included delay in seeking care due to the need to obtain husbands' permission and financial support, the perceived cost and real cost of travel, particularly due to costs associated with referral of severely ill children to a further facility and repeated travel due to health post closure [21]. Supply-side barriers included frequent stock-outs of medicines and other necessary supplies, service interruption and inconsistent operating hours at health posts [24]. Further, it showed that HEWs had poor skills and confidence [25], especially when managing and treating newborns [26], lack of local government ownership and lack of accountability for both the CBNC and iCCM programs, and inconsistent supervision and monitoring.…”
Section: Barrier Analysismentioning
confidence: 99%